(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Pharmaceuticals, including antibiotics and heavy metals, are emerging contaminants in many African countries affecting all facets of life as a result of indiscriminate disposal. Objectives: This study evaluates the presence and potential health risks of pharmaceuticals in catfish from western Nigeria. Material and Methods: Ten Fish samples were collected from local markets and aquaculture farms. Antibiotic and heavy metal residues were analysed using solid-phase extraction (SPE) and high-performance liquid chromatography (HPLC) and Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) respectively. Results: Seven antibiotics were tested: Trimethoprim (TM), Tetracycline (TC), Ciprofloxacin (CP), Sulfamethoxazole (SZ), Enrofloxacin (EN), Metronidazole (MT), and Ampicillin (AP). TM, TC, CP, SZ, EN, and AP were detected. TC was found at 0.2 µg/g, exceeding the maximum residue limits (MRLs). CP, SZ, EN, and AP averaged 0.1 µg/g, also above MRLs. TM was below MRLs at 0.05 µg/g, and MT was absent in all samples. On the other hand, the levels of Iron, Zinc, and Chromium present in all samples ranged from 6.0196 to 846.8667 mg/kg, 0.3985 to 579.4926 mg/kg and 0.2336 to 18.8947 mg/kg respectively, well above the EU’s maximum safe level of 5 mg/kg. Arsenic, Manganese Copper, Cobalt, Arsenic have concentrations below the maximum safe level. All samples were Lead (Pb)-free which conforms to the EU specification. Conclusion: The findings confirm that antibiotics and heavy metals are significant contaminants in catfish. This highlights the urgent need for legislation to control pharmaceutical waste, regulate antibiotic use in aquaculture, and implement stringent screening and monitoring measures to safeguard public and aquatic life.